Karakteristik Fisik Briket Tempurung Kelapa Menggunakan Perekat Tepung Tapioka - Ansar Ansar; Diah Ajeng Setiawati; Murad Murad; Baiq Sulasi Muliani (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Briquette is one of the alternative biomass fuels as a substitute for fossil energy. To produce high-quality briquettes is requires printing equipment effectively and efficiently. Therefore, this study aims to obtain the best treatment to make briquettes from coconut shells. Briquetting is made by using 4 pumping variations, namely 4, 6, 8, and 12 times. The parameters observed were hardness, percentage of destruction, moisture content, and the flame of briquettes. The results showed that the best coconut shell briquettes were found in pumping treatment 12 times with an average hardness of 27.7 kg / cm2, percentage of destruction 18.50%, moisture content of 4.55% and the flame of 112.61 minutes. While the worst quality was obtained at pumping 4 times with an average hardness of 16.5 kg / cm2, the percentage of destruction was 43.36%, moisture content was 7.92%, and flame 111.34 minutes.